Escalating incidence of eosinophilic esophagitis in Canton of Vaud, Switzerland, 1993–2013: a population‐based study. Issue 12 (13th September 2015) - Giriens, B.; Yan, P.; Safroneeva, E.; Zwahlen, M.; Reinhard, A.; Nydegger, A.; Vavricka, S.; Sempoux, C.; Straumann, A.; Schoepfer, A. M.
Abstract: Background: Eosinophilic esophagitis (EoE) is a chronic, inflammatory disease of the esophagus with a rapidly increasing incidence. However, population‐based epidemiologic data on EoE are rare and limited to regions with less than 200 000 inhabitants. We evaluated the incidence and prevalence of EoE over time in Canton of Vaud, Switzerland. Materials and methods: Canton of Vaud lies in the French‐speaking, Western part of Switzerland. As of December 2013, it had a population of 743 317 inhabitants. We contacted all pathology institutes ( n = 6) in this canton to identify patients that have been diagnosed with esophageal eosinophilia between 1993 and 2013. We then performed a chart review in all adult and pediatric gastroenterology practices to identify patients with EoE. Results: Of 263 patients with esophageal eosinophilia, a total of 179 fulfilled the diagnostic criteria for EoE. Median diagnostic delay was 4 (IQR 1–9) years. No patient was diagnosed with EoE prior to 2003. Incidence of EoE increased from 0.16/100 000 inhabitants in 2004 to 6.3/100 000 inhabitants in 2013 ( P < 0.001). The cumulative EoE prevalence in 2013 was 24.1/100 000. The incidence in males was 2.8 times higher (95% CI 2.01–3.88, P < 0.001) when compared to that in females. The annual EoE incidence was 10.6 times higher (95%‐CI 7.61–14.87, P < 0.001) in the period from 2010 to 2013 when compared to that in the period from 1993 to 2009. Conclusions: The incidence and cumulative prevalence of EoE in Canton of Vaud, Switzerland, has rapidly increased in the past 10 years.